THE INFLUENCE OF ENGLISH ON THE TERMINOLOGY IN THE DOMAIN OF BANKING AND FINANCE: ROMANIAN, RUSSIAN AND GERMAN - Gobjila, Natalia (CEP USM, 2017)
This paper aims at examining the influence of English as a lingua franca on the terminology in the domain of banking and finance, which becomes more and more globalised with the increased prevalence of transnational financial operations. The analysis of examples from Romanian, Russian and German is intended to illustrate how English terminology is introduced in different languages, mainly through borrowing and loan translation or calque, and also adapted to the grammatical and structural peculiarities of the target language.

În lucrare este examinată influența limbii engleze ca lingua franca asupra terminologiei din domeniul bănci şi finanţe, care, odată cu creșterea volumului de operațiuni financiare transnaționale, devine din ce în ce mai globalizat.Analiza exemplelor din limbile română, rusă și germană are scopul de a ilustra modul în care terminologia engleză este introdusă în diferite limbi, în principal prin împrumut și calc, adaptate particularităților gramaticale și structurale ale limbii-țintă.
INFLUENŢA LIMBII ENGLEZE ASUPRA TERMINOLOGIEI DIN DOMENIUL BĂNCI ŞI FINANŢE: LIMBILE ROMÂNĂ, RUSĂ ŞI GERMANĂ
Keywords: globalization; terminology; borrowing; globalizare; terminologie; calc